2021
DOI: 10.26594/register.v8i1.2327
|View full text |Cite
|
Sign up to set email alerts
|

The influence of familiarity and personal innovativeness on the acceptance of fintech lending services: A perspective from Indonesian borrowers

Abstract: Financial Technology (FinTech) Lending in Indonesia is an innovative solution for financial services in Indonesia because it has convenience and benefits for Indonesians who need loans, fund management, and other financial transaction activities. FinTech Lending is growing fast because it offers reasonable interest rates and access to conventional financial institutions. The growth of FinTech Lending is expected to support financial inclusion planned by the Indonesian government. In 2020, 126 FinTech Lending C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Personal innovativeness matches with the outcome of Wirani et al (2022).Convenience is closely related with the output by Zhang & Kim (2020). Finally, fintech adoption has shown a positive effect on financial inclusion which is same as the research results from Goswami et al (2022)…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Personal innovativeness matches with the outcome of Wirani et al (2022).Convenience is closely related with the output by Zhang & Kim (2020). Finally, fintech adoption has shown a positive effect on financial inclusion which is same as the research results from Goswami et al (2022)…”
Section: Discussionsupporting
confidence: 85%
“…PI shown a significant influence on acceptance of fintech Tun-Pin et al (2019). With respect to financial technology services, research study by Wirani et al (2022) among Indonesian borrowers proved a positive influce on PI acceptance on fintech. H5: Personal innovativeness has a positive effect on adoption of fintech services.…”
Section: Personal Innovativeness (Pi)mentioning
confidence: 98%
“…PI is also found to be significant predictor of DBAI for both set of respondents, accepting H8a finding its support from studies of Yuan and Ma (2022); Wirani et al (2022). However, there is significant difference in PI among female bank employees (β = .720, p = .000) and female IT employees, (β = .804, p = .000) being its loading much higher in case female IT employees.…”
Section: Discussionmentioning
confidence: 51%
“…Familiarity with the application will determine the level at which the e-wallet application is widely adopted and recognized. A study by Wirani [34] explained that customers' propensity to use Fintech services in Indonesia is influenced by the reliability of service providers with a precise and reputable reputation. It was also found that familiarity has a negative effect related to user privacy concerns [9].…”
Section: A Research Model and Hypotheses Developmentmentioning
confidence: 99%